Evaluation of phytochemical composition and metabolite profiling of macroalgae Caulerpa taxifolia and C. peltata from the Banda Aceh coast, Indonesia - SAID ALI AKBAR; MUHAMMAD HASAN; SARI AFRIANI; CUT NUZLIA (Society for Indonesian Biodiversity, 2023)
Abstract. Akbar SA, Hasan M, Afriani S, Nuzlia C. 2023. Evaluation of phytochemical composition and metabolite profiling of macroalgae Caulerpa taxifolia and C. peltata from the Banda Aceh coast, Indonesia. Biodiversitas 24: 5283-5292. The study of seaweeds to extract their bioactive compounds has become increasingly important from the standpoint of broader applications. This study aimed to examine the metabolite profiles and phytochemical content of Caulerpa peltata and Caulerpa taxifolia along the coast of Banda Aceh in Indonesia. Readers interested in learning more about the biological activities of C. peltata and C. taxifolia can refer to the material gathered from this study. The three steps proposed by this study were phytochemical composition, antioxidant scavenging, and in vivo metabolite profiling by the use of Gas Chromatography-Mass Spectrometry (GC-MS), Fourier Transform Infrared (FTIR) characterization, and the 2,2-diphenylpicrylhydrazyl (DPPH) test. Using DPPH to measure antioxidant activity, both extracts demonstrated greater scavenging capability, with inhibition values of 42.59% and 39.81%, respectively. In both macroalgae, the GC-MS methodology has shown to be a quick, sensitive, and trustworthy way to monitor individual components and the entire chemical composition. In C. taxifolia, there are 29 phytochemical compounds, whereas in C. peltata, there are 26 types. The ethanol extract of the macroalgae C. taxifolia and C. peltata was then subjected to an FTIR spectrum. These findings at 3352 cm-1, 1654 cm-1, and 1019 cm-1 proved that alkanes, alkenes, and hydroxyl groups were present, corresponding to several compounds in the GC-MS measurement results. Caulerpa taxifolia and C. peltata are potential antibacterial agents; the bioactive compounds for this activity are Heptadecane, Hexadecanoic acid, and other ester derivatives.